Effect of Feeding Oak Acorn on Expression of IL-2, IL-13 and IFN-γ Genes in Bursa Fabricius Tissue of Broiler Chickens (Short Communication) - Nobakht E (Poultry Science Journal, 2019)
Today, the use of oak as a replacement feed in poultry diets is well documented. However, oak contains polyphenol compounds (tannins) as antinutrient factors resulted in limited usage in the poultry rations. Generally, consumption of feeds containing tannin could affect gene expression level of immune system. Therefore, the aim of this study was to investigate the effect of different levels of oak acorn on the expression of interferon-γ (IFN-γ), interleukin-2 (IL-2) and interleukin-13 (IL-13) genes in the bursa Fabricius tissue of broiler chickens. For this purpose, broiler chickens were fed with diets containing 0 (control), 15% and 20% oak acorn in 6 weeks experimental period. Total RNA was extracted from bursa Fabricius tissue of 6 chickens for each treatment (18 broiler chickens) on day 42. To investigate the expression of IL-2, IL-13 and IFN-γgenes, their expressions were normalized with β-actin gene as a reference gene. REST, 2009, V2.0.13 software was used for analysis of gene expression data. The results showed that the expression levels of IL-2 and IL-13 genes in bursa Fabricius tissue were not significantly different for 15% oak acorn treatment compare to control group, but the mRNA expression levels of IL-2 and IL-13 were significantly lower in 20% of oak acorn in respect to control and 15% oak acorn diets (P < 0.05). However, expression of IFN-γ gene was not observed in any samples of the three treatments. According to the results of this study, it seems that increasing the amount of oak acorn in diet of broiler chicken with increase tannin content most likely could suppress the expression of IL-2 and IL-13 genes in bursa Fabricius tissue.